Feta and related cheeses - Robinson, R. K. (Richard Kenneth); Tamime, A. Y. (Ellis Horwood series in food science and technology., 1996)
This book provides a detailed guide to white brined cheeses: raw materials, processes, manufacture, equipment and packaging, chemistry, microbiology and sensory specifications. It includes comprehensive coverage of the production, maturation and distribution of cheeses such as Feta, Domiati and Halloumi as well as many more local varieties.